Qualitative and quantitative validation of an instrument to measure university student satisfaction (Innovaciones Educativas, 2021)
The main objective of this research is to validate qualitatively and quantitatively the instrument to measure the satisfaction of university students with their education (SEUE). This instrument was developed by Gento and Vivas (2003), and will be used later to evaluate the perception of Engineering students of the University of Zulia, in order to determine the relationships between satisfaction with respect to the variables measured and their academic performance. To achieve this objective, the previously designed instrument was submitted to expert judgment to determine its qualitative validity, and thus make the necessary modifications, to then apply it to a probabilistic sample composed of 336 subjects from a total population of 2653 active students of the School of Engineering of the University of Zulia. With these data, the reliability of the instrument was calculated using Cronbach’s Alpha and the Pearson correlation test was carried out. Subsequently, an exploratory factor analysis was carried out to determine the validity of the construct and to reduce the dimensions initially designed, to later calculate the criterion validity (concurrent validity) using a standard instrument. Finally, the stability and performance of the instrument was determined. At the end, it was possible to conclude that the dimensions could be reduced to six and the University Student Satisfaction could be measured by means of this instrument, since it proved it possesses stability and reproducibility to be used in future research.
Keywords: measurement method; measuring instrument; satisfaction; college student; education